Uranium dynamics and developmental sensitivity in rat kidney. Issue 7 (26th April 2013) - Homma‐Takeda, Shino; Kokubo, Toshiaki; Terada, Yasuko; Suzuki, Kyoko; Ueno, Shunji; Hayao, Tatsuo; Inoue, Tatsuya; Kitahara, Keisuke; Blyth, Benjamin J.; Nishimura, Mayumi; Shimada, Yoshiya
ABSTRACT Renal toxicity is the principal health concern after uranium exposure. Children are particularly vulnerable to uranium exposure; with contact with depleted uranium in war zones or groundwater contamination the most likely exposure scenarios. To investigate renal sensitivity to uranium exposure during development, we examined uranium distribution and uranium‐induced apoptosis in the kidneys of neonate (7‐day‐old), prepubertal (25‐day‐old) and adult (70‐day‐old) male Wistar rats. Mean renal uranium concentrations increased with both age‐at‐exposure and exposure level after subcutaneous administration of uranium acetate (UA) (0.1–2 mg kg–1 body weight). Although less of the injected uranium was deposited in the kidneys of the two younger rat groups, the proportion of the peak uranium content remaining in the kidneys after 2 weeks declined with age‐at‐exposure, suggesting reduced clearance in younger animals. In situ high‐energy synchrotron radiation X‐ray fluorescence analysis revealed site‐specific accumulation of uranium in the S3 segment of the proximal tubules, distributed in the inner cortex and outer stripe of the outer medulla. Apoptosis and cell loss in the proximal tubules increased with age‐at‐exposure to 0.5 mg kg–1 UA. Surprisingly, prepubertal rats were uniquely sensitive to uranium‐induced lethality from the higher exposure levels. Observations of increased apoptosis in generating/re‐generating tubules particularly in prepubertal rats could help to explain their high mortality rate. Together, our findings suggest that age‐at‐exposure and exposure level are important parameters for uranium toxicity; uranium tends to persist in developing kidneys after low‐level exposures, although renal toxicity is more pronounced in adults. Copyright © 2013 John Wiley & Sons, Ltd.